Is the Precautionary Principle a Midlevel Principle?. Issue 1 (2nd January 2019) - Sandin, Per; Peterson, Martin
ABSTRACT: In this article, we defend two claims about the precautionary principle. The first is that there is no 'core' precautionary principle that unifies all its different versions. It is more plausible to think of the different versions as being related to each other by way of family resemblances. So although precautionary principle x may have much in common with precautionary principle y, and y with z, there is no set of necessary and sufficient conditions that unify all versions of the principle. Our second claim is that it is sometimes appropriate to think of the precautionary principle as a midlevel principle in the sense proposed by Beauchamp and Childress in their Principles of Biomedical Ethics, i.e. as a non-rigid moral principle. We argue that if the precautionary principle is conceived as a non-rigid principle that needs to be balanced against other principles before a moral verdict can be reached, then this enables us to address some standard objections to the principle.